Pengaruh Variabel Makro Ekonomi Terhadap Indeks Harga Saham di Jakarta Islamic Indexs (JII) Periode 2017-2021 - In'am Aulia Akbar; Citra Mulya Sari (Jurnal Akuntansi dan Pajak, 2023)
This study aims to analyze the effect of macroeconomic variables on the stock price index in the Jakarta Islamic Indexs (JII) for the 2017-2021 period. This research uses a quantitative approach and belongs to the type of associative research. The population in this study is the Jakarta Islamic Index (JII) data, inflation, the BI 7-Day repo rate, changes in the IDR/USD exchange rate and the money supply (M2). The sampling technique used in this research is purposive sampling. The d This study aims to analyze the effect of macroeconomic variables on the stock price index in the Jakarta Islamic Indexs (JII) for the 2017-2021 period. This research uses a quantitative approach and belongs to the type of associative research. The population in this study is the Jakarta Islamic Index (JII) data, inflation, the BI 7-Day repo rate, changes in the IDR/USD exchange rate and the money supply (M2). The sampling technique used in this research is purposive sampling. The data used as a sample is the Jakarta Islamic Index (JII) closing price data and all research variable data using monthly data, so that 60 observation periods are obtained from January 2017 to December 2021. The data analysis technique used is multiple linear regression analysis. The results of this study indicate that inflation and the BI 7-Day repo rate partially have a significant negative effect on the Stock Price Index in the Jakarta Islamic Indexs (JII) for the 2017-2021 period. While the IDR/USD Exchange Rate and the Total Money Supply partially have a significant positive effect on the Stock Price Index in the Jakarta Islamic Indexs (JII) for the 2017-2021 Period. Based on the results of the f-test of inflation variables, the BI 7-Day repo rate, the IDR/USD exchange rate and the money supply (X4) simultaneously have a significant effect on the Stock Price Index in the Jakarta Islamic Indexs (JII) for the 2017-2021 period with a determinant coefficient of 81.1 %.